Tauopathy and Movement Disorders—Unveiling the Chameleons and Mimics - Ganguly, Jacky; Jog, Mandar (Frontiers in Neurology, 2020)
The spectrum of tauopathy encompasses heterogenous group of neurodegenerative disorders characterized by neural or glial deposition of pathological protein tau. Clinically they can present as cognitive syndromes, movement disorders, motor neuron disease or mixed. The heterogeneity in clinical presentation, genetic background and underlying pathology make it difficult to classify and clinically approach tauopathy. In the literature, tauopathies are thus mostly highlighted from pathological perspective. From clinical standpoint, cognitive syndromes are often been focussed while reviewing tauopathies. However, the spectrum of tauopathy has also evolved significantly in the domain of movement disorders and has transgressed beyond the domain of primary tauopathies. Secondary tauopathies from neuroinflammation or autoimmune insults and some other ‘novel’ tauopathies are increasingly being reported in the current literature, while some of them are geographically isolated. Because of the overlapping clinical phenotypes, it often becomes hard for the clinician to diagnose them clinically and have to wait for the pathological confirmation by autopsy. However, each of these tauopathies has some clinical and radiological signatures those can help in clinical diagnosis and targeted genetic testing. In this review, we have exposed the heterogeneity of tauopathy from a movement disorder perspective and have provided a clinical approach to diagnose them ante mortem before confirmatory autopsy. Additionally, phenotypic variability of these disorders (chameleons) and the look-alikes (mimics) have been discussed with potential clinical pointers for each of them. The review provides a framework within which new and as yet undiscovered entities can be classified in the future.